Detection of Mycobacterium tuberculosis DNA in intraocular fluid of 11 suspected tuberculous uveitis patients by multiplex PCR - Huirong Xu; Min Xu; Fang Chen; Hong Chen; Wei Du; Jing Yu (BMC Ophthalmology, 2025)
Abstract Background This study aims to detect Mycobacterium tuberculosis complex (MTBC) DNA in intraocular fluid from clinically suspected tuberculous uveitis patients using multiplex polymerase chain reaction (PCR) and investigate the diagnostic utility of multiplex PCR for tuberculous uveitis. Methods Primers targeting three specific genes (MPB64, CYP141, and IS6110) within the MTBC genome were designed. Multiplex PCR was conducted using DNA from the H37Rv strain as well as DNA extracted from fluids of confirmed tuberculosis patients to assess primer specificity and method feasibility. Intraocular fluid samples were collected during the initial visit for multiplex PCR detection of MTBC DNA. The results of multiplex PCR tests were correlated with intraocular fluid findings and clinical profiles of patients clinically diagnosed with tuberculous uveitis who underwent standard antituberculosis therapy. Results Multiplex PCR was employed to detect MTBC DNA in intraocular fluid samples from 15 patients clinically suspected of having tuberculous uveitis, with no amplification bands observed in the DNA lanes for the three target genes. T-cell spot test (T-SPOT) results were positive in 11 patients (100%), while purified protein derivative (PPD) tests were positive in 5 patients (45.5%). Abnormal chest CT findings were noted in 4 patients (36.4%), including one case of active pulmonary tuberculosis and three cases of inactive pulmonary tuberculosis. Retinal vasculitis was observed in 6 eyes (46.2%), panuveitis in 5 eyes (38.5%), and intermediate uveitis in 2 eyes (15.4%). The average duration of antituberculosis therapy administered to the 11 patients was 7.1 months (range: 6–10 months). The medium LogMAR Best Corrected Visual Acuity (BCVA) significantly improved at the last follow-up (Z=-2.371, P = 0.018). Conclusions Standard antituberculosis therapy demonstrated effectiveness in treating 11 patients clinically suspected of having tuberculous uveitis despite the absence of detectable MTBC DNA in intraocular fluid via multiplex PCR. Further investigation is warranted to elucidate the role of PCR in diagnosing ocular tuberculosis among Chinese individuals.